Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae) - Bortoluzzi, Sidnei; Caron, Edilson; Ribeiro-Costa, Cibele S. (Zootaxa, 2017)
The rove beetle genus Hypotelus Erichson, 1839 is one of seven extant genera of a subfamily with a historically misinterpreted concept, status and phylogenetic position. The genus comprises minute species that have been found under the bark of trees or in leaf litter mainly in Neotropical forests. The major aim of this study was to test the monophyly of this genus based on adult morphology and to review its species. Cladistic analyses were performed and Hypotelus is a monophyletic genus supported by 8 synapomorphies and includes five new species: H. brevitarsus sp. nov., H. castaneus sp. nov., H. corniculatus sp. nov., H. melanodelta sp. nov. and H. scheerpeltzi sp. nov. Additionally, all species are described/redescribed and illustrated, most of them for the first time. An identification key, geographical records and natural history data for each species are also provided.